Um framework para plataformas de microserviços distribuídos - ALCÂNTARA, Luiz Eduardo Alves de (2020)
The efforts to transform a generic programming language like Java in a complete tool to develop Web applications has been turning too hard to keep following its growing learning curve because of its many coupled frameworks which have become standard development. It’s a difficult path to change, due to its popularity in many segments, reinforced by the aggressive marketing of giants like Oracle, its current owner. This paperwork proposes, in counterpart, the use of distributed platforms into Microservices and API independent functions (inclusive for database access) in which the implementations should follow the specifications of a framework designed to have a low learning curve, fast development, higher economy of IT resources and full compatibility with all platforms developed under its guidelines, independently of each programming languages will be used, both for the implementation of the platform and for the services provided, which may belong to any standard market category, such as user management and authenticated access, cryptograph that is strong and protocol independent, file repository and intelligent storage management, synchronous and asynchronous distributed communication through messaging, dynamic user interface modeling, Real-time multimedia streaming and execution of database procedures with a direct return to client layer.